The reformulation on detachment markers in the PRESEEA corpus of Santiago, Chile - San Martín Núñez, Abelardo (Boletín de Filología, 2013)
The aim of this paper is to extend our approach, in San Martín (2004-2005), to a specific type of discourse marker in spoken Spanish in Santiago de Chile from variationist point of view: the reformulation of detachment markers. For this purpose, the particles that met the above function in a sample of 54 interviews that make up the Sociolinguistic Corpus of PRESEEA in Santiago, Chile were identified. On the one hand, we analyze the behavior of such markers in the range indicated above and, on the other hand, we provide the distribution of employment in a socially stratified sample of Santiago's speakers. For the study of these particles, the Martin Zorraquino & Portolés (1999) and Portolés (2001) concept and classification of discourse markers, and the suggestions of Cortes (1988) and Carbonero & Santana (2010) for his social quantitative analysis, is applied. The analysis considered the "reformulation of detachment" as a sociolinguistic variable with the following values or variants (markers): igual, de todas maneras, en todo caso y de todas formas. Consequently, socio-demographic factors were correlated with subjects' use of suchmarkers. Thus, based on the functional-pragmatic commutability of discourse markers registered it preceded its quantitative analysis according to the variables: age, sex-gender and educational level ofthe interviewees.